The dynamics governance of renewable energy in rural: Insights from Indonesia - Werang, Maria Lusiana Florentin; Putri, Rizky Amalia; Likuwatan Werang, Nicolaus Petrus (Social, Ecology, Economy for Sustainable Development Goals Journal, 2026)
Background: Renewable energy in rural areas is a complex issue with interactive effects, thus reveals the dynamics of governance barriers in Indonesia that have not been resolved since the responsibility through the Sustainable Development Goals (SDG) initiative framework was delegated to local (rural) governments to be actualized in the field, but if seen in reality the results have not been significant, so that the expected goals have not been achieved consistently. Methods: The study applied a qualitative descriptive approach and content analysis to investigate, comprehend, and analyze the dynamic governance of renewable energy in rural areas, with a special focus on Indonesia. Finding: The key findings reveal that crumbling governance is the main issue at the central-local level structure in actualizing the renewable energy initiative. Hence, policy misalignment, duplicated efforts, and inefficient initiatives affect the governance dynamics. Conclusion: The study concludes that the Indonesian government (central-local) must intensify the institutional frameworks, foster stakeholder collaboration, simplify regulatory processes, and assist local capacity building to move forward. These steps will enable more efficient, responsive, and sustainable renewable energy governance in rural areas. Novelty/Originality of this article: The novelty contributes to the broad scientific implications of renewable energy as a governance framework to elicit prosperity for the community in rural areas of Indonesia and other developing countries based on the Sustainable Development Goals (SDGs) for affordable and clean energy prospects.